Hydrolysis of p-nitrophenyl perfluoroctanoate in mixed surfactant systems - Torres, María Florencia (2014)
The kinetics of the hydrolysis reaction of p-nitrophenyl perfluoroctanoate were studied in the presence of different amphiphilic systems: two hydrocarbon surfactants (sodium dodecyl sulfate, SDS, and polyoxyethylene(23)lauryl ether, Brij-35), a perfluorinated detergent (perfluorononanoic acid, PFNA) and in mixtures of SDS–PFNA and Brij-35–PFNA. The study was performed at different compositions of the mixtures (characterized by the molar fraction of PFNA, αPFNA), and for each αPFNA the concentration was varied over a wide range. The kinetic probe p-nitrophenyl perfluoroctanoate showed a very strong interaction with the surfactants. In the presence of the mixed surfactants, the behaviour of the probe changed dramatically with the composition of the mixtures, which indicates that this substrate is very sensitive to the effect of the micellar media, being a very good molecule to study these types of surfactant systems. The use of the studied ester allowed us to confirm the presence of two different aggregates in the mixture Brij-35–PFNA as was previously observed with other techniques. The presence of hydrocarbon-rich micelles at low αPFNA, as well as perfluorinated rich micelles at high αPFNA was also confirmed. The kinetic behaviour of p-nitrophenyl perfluoroctanoate in SDS–PFNA mixtures fully agreed with our previous description of the aggregates formed in this system. The presence of a practically pure PFNA micelle at high αPFNA could be also demonstrated from the kinetic results.